Correcting the parameters of the "mochtor-film" system for multiformat chambers in medicine - Балашов, С. В.; Ясенко, С. А. (Proceedings of National Aviation University (archive), 2002)
The questions of formation of high-quality X-ray images during transferring them to a film in multiformat chambers are considered. An algorithm for correction of a digital image before the exposure to a film is proposed